Changes in physical activity trends and the health status in south Korean adult males before and during the COVID-19 pandemic - Su Yeon Roh; Kyu Jin Jin; Ik Young Chang (Journal of Men's Health, 2023)
This study aims to investigate changes in physical activity and health trends before and during the COVID-19 pandemic in Korea using data from the 2019, 2020, and 2021 Korea National Sports Participation Survey (KNSPS). A total of 15,656 adult males (5487 people in 2019, 4791 people in 2020, and 5378 people in 2021) were selected for this research. Descriptive statistical analysis, chi-square test, and one-way analysis of variance were performed. In this study, we revealed changes in sports activities, participation levels, health and fitness status perception, and health and fitness maintenance factors of Korean adults before and after the COVID-19 pandemic. Specifically, the participation rate in outdoor sports activities, such as walking, gate ball, golf, and fishing has increased compared to before the COVID-19 outbreak. On the other hand, the participation rate of indoor sports activities, such as bodybuilding, swimming, yoga, and Pilates showed a decreasing trend. Participation period, frequency, and intensity, which evaluate the level of sports participation, also showed significant differences during COVID-19, but as the sports participation levels have not changed regularly, it cannot be attributed to COVID-19. Finally, health and fitness status perception were found to be worse after the COVID-19 outbreak than before. In addition, the rate of considering regular physical activity participation as a factor to maintain health and fitness after the COVID-19 outbreak increased. The results of this study can be used as basic data to recognize the impact of the pandemic on our lives and promote healthy and regular physical activity in preparation for any pandemic that may occur in the future.